Turbulent Mixing in a Loop Current Eddy From Glider‐Based Microstructure Observations. Issue 14 (13th July 2020) - Molodtsov, S.; Anis, A.; Amon, R. M. W.; Perez‐Brunius, P.
Abstract: Turbulence parameters have been estimated from microstructure velocity and temperature measurements in an anticyclonic Loop Current Eddy in the Gulf of Mexico for the very first time. Measurements were performed during a mission in October 2016, using a G2 Webb Research Slocum ocean glider instrumented with a microstructure sensors suite. Well‐defined turbulent kinetic energy dissipation rate patterns in the eddy and the surface mixed layer were clearly identified from both the velocity and temperature microstructure data. Higher dissipation rates were observed at the flanks and beneath the eddy core (up to 10 −7 W/kg), while the core interior appeared to be very quiescent ( 10 −11 W/kg). Double diffusive thermohaline intrusions were detected on the side of the eddy, while the region below the eddy core was more conducive for salt fingering. Heat and salt fluxes associated with these processes suggest that a life span of such an eddy is 1.5 years. Plain Language Summary: Mixing intensity in the ocean is often observed using microstructure measurements that target small‐scale processes such as microvelocity shear and temperature fluctuations. This study targets a ubiquitous and important feature of the Gulf of Mexico, namely, Anticyclonic Loop Current Eddies. Here we report, for the first time, on physical processes in such an eddy surveyed with a state‐of‐the‐art microstructure sensors suite mounted on an autonomous ocean glider. Key Points: Temperature microstructure data allow reliable estimation of very low turbulent kinetic energy dissipation rates Glider‐based microstructure measurements were conducted for the first time in a large mesoscale anticyclonic eddy Double diffusion processes associated with eddy dynamics were observed with microstructure and CTD data